2019
DOI: 10.1016/j.electacta.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Porous Ni3S4/C aerogels derived from carrageenan-Ni hydrogels for high-performance sodium-ion batteries anode

Abstract: Ni 3 S 4 /C aerogels derived from carrageenan-Ni hydrogels for high-performance sodium-ion batteries anode, Electrochimica Acta (2019), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In the case of anode materials, the research have exhibited a trend of blowout development. Carbon, alloys, transition‐metal oxides/sulfides have been extensively explored as promising anodes of SIBs . Among these materials, carbon have gained increasing research attentions as a kind of resource abundant, conductive, and thermodynamically stable material .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of anode materials, the research have exhibited a trend of blowout development. Carbon, alloys, transition‐metal oxides/sulfides have been extensively explored as promising anodes of SIBs . Among these materials, carbon have gained increasing research attentions as a kind of resource abundant, conductive, and thermodynamically stable material .…”
Section: Introductionmentioning
confidence: 99%
“…The carbon skeleton in this nanostructure not only facilitates the fast charge transfer reaction but also enhances the mechanical properties of FeS nanoparticles and buffers their volume changes, thereby extending the electrode cycle life. Moreover, Ni 3 S 4 nanoparticles were embedded in porous carbon ( Figure 8 b,c) [ 118 ]. As a negative electrode for Na-ion batteries, it maintained a capacity of 297 mAh g −1 for 100 cycles at a current density of 1 A g −1 .…”
Section: Different Structures and Components Of Biomass-derived Carbo...mentioning
confidence: 99%
“…In conclusion, metals are intercalated into biomass-derived carbon as active materials, providing more active sites, while biomass carbon limits the volume change during the intercalation/deintercalation of sodium ions through internal stress. The synergy between the two together improves the stability and electrochemical performance of Na-ion batteries [ 32 , 114 , 118 , 119 , 120 ].…”
Section: Different Structures and Components Of Biomass-derived Carbo...mentioning
confidence: 99%
“…Carrageenan is widely used in diverse applications such as food, pharmaceutical and cosmetic industries. Due to their availability and surface properties, their broad functionality, low toxicity, biocompatibility, and biodegradability, carrageenan porous materials and aerogels are very promising in tissue engineering, drug delivery, environmental remediation catalysis, and many other applications [255][256][257][258][259][260][261][262][263][264][265]. Abdellatif et al showed that freeze-drying of ι-carrageenan results in porous materials with a macroporous structure [260].…”
Section: Aerogels From Carrageenanmentioning
confidence: 99%